Lipids in major depressive disorder: new kids on the block or old friends revisited? - van der Heijden, Anna Rosa; Houben, Tom (Frontiers in Psychiatry, 2023)
Major depressive disorder (MDD) is a psychiatric mood disorder that results in substantial functional impairment and is characterized by symptoms such as depressed mood, diminished interest, impaired cognitive function, and vegetative symptoms such as disturbed sleep. Although the exact etiology of MDD is unclear, several underlying mechanisms (disturbances in immune response and/or stress response) have been associated with its development, with no single mechanism able to account for all aspects of the disorder. Currently, about 1 in 3 patients are resistant to current antidepressant therapies. Providing an alternative perspective on MDD could therefore pave the way for new, unexplored diagnostic and therapeutic solutions. The central nervous system harbors an enormous pool of lipids and lipid intermediates that have been linked to a plethora of its physiological functions. The aim of this review is therefore to provide an overview of the implications of lipids in MDD and highlight certain MDD-related underlying mechanisms that involve lipids and/or their intermediates. Furthermore, we will also focus on the bidirectional relationship between MDD and the lipid-related disorders obesity and type 2 diabetes.